Comparative quality assessment of edible and blended edible oils (Journal of Oilseed Brassica, 2026)
The chemical and physical properties of oils are amongst the most important properties that determine the quality and help to describe the present condition of oils. The soybean oil used as based oil for replacement. The soybean oil was replaced by (40-85); mustard, sunflower and groundnut are each (5-20%). pH of individual and blended oil was ranged between 3.2 to 5.4, density (0.892 to 0.900), Specific gravity (0.8363 to 0.8391), Free fatty acid (0.14 to 0.19), Iodine value (2.20 to 2.22), Peroxide value (0.16 to 0.34), pH, density, Sp. gravity, Iodine value, FFA, Peroxide value of individual as well as blended oil was increased with increase the storage period under different storage condition. This affects was seen as replacement of soybean oil from other oil i.e. sunflower, groundnut and mustard oil. The storage oils at room temperature affect the quality of oil during storage.